Comparing Effects of Green Innovation and Renewable Energy on Green Economy: The Metrics of Green Economy as Nucleus of SDGs - Younas, Somia; Shoukat, Sana; Awan, Ayesha; Arslan, Syed Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
Green Economy (GE) is a practicable strategy for the implementation of a sustainable development paradigm that confirms a dynamic growth, which is both humanly and naturally sustainable. The objective of this research article is to analyze the effect of environment friendly variables like green innovations (GI) and Renewable Energy (GN) specifically along with some variables on GE in South Asia (SA). This research article discusses a relationship of renewable energy (GN), green jobs (GJ), natural resource scarcity (RS), green innovations and green technology (GT) on GE. To evaluate the status of the connection between the variables, a panel autoregressive distributed lagged (ARDL) bounds analysis methodology was used on 50 years (1972 – 2021) data of South Asian region. This is a panel data analysis as countries of South Asia were discussed. Findings of this study showed no influence of GI on GE as well as on sustainable development. Furthermore, linked variable Renewable Energy indicated positive effect on GE along with economic development. On the contrary, the results of green jobs, GT and resource scarcity are not in the favor of GE because of lack of knowledge, cost of production, less awareness etc. On account of these empirical findings attained, policy strategies are recommended to introduce new skylines for economically underdeveloped nations in agrarian and industrialization. Government can take steps to create opportunities through trainings for a layperson to participate in economic activities and live with a respectable employment. Awareness campaigns, degrees, diplomas, certified training programs and workshops should be organized to implement this initiative by its spirit.